If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(x + 1) = 3x + -15 Reorder the terms: 2(1 + x) = 3x + -15 (1 * 2 + x * 2) = 3x + -15 (2 + 2x) = 3x + -15 Reorder the terms: 2 + 2x = -15 + 3x Solving 2 + 2x = -15 + 3x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-3x' to each side of the equation. 2 + 2x + -3x = -15 + 3x + -3x Combine like terms: 2x + -3x = -1x 2 + -1x = -15 + 3x + -3x Combine like terms: 3x + -3x = 0 2 + -1x = -15 + 0 2 + -1x = -15 Add '-2' to each side of the equation. 2 + -2 + -1x = -15 + -2 Combine like terms: 2 + -2 = 0 0 + -1x = -15 + -2 -1x = -15 + -2 Combine like terms: -15 + -2 = -17 -1x = -17 Divide each side by '-1'. x = 17 Simplifying x = 17
| 10y-2=3y+33 | | 3(5+4b)-2=0 | | 3z-4=5z-1 | | 4+a=16 | | 82=2(-1+7m) | | 7+3.2=3.2x | | 2b+8=0 | | 6y-4(2-3(4y-1))=-17 | | A+81=9z-7 | | 7b+13=35-4b | | 166=2*36+2W | | 27x^2+37x=0 | | 3=2(-2)-y | | 4x-12=3.5 | | 10+x=1x+2 | | 3(x+4)-2=3x+10 | | 2x-4y+-6=0 | | 6y+15=9y | | 2u+10=20 | | 3b*c= | | 2x^3-12x^2+24x-14=0 | | 8x-x^2-15=0 | | 2x+4=8x-1 | | y+3=4(x-1) | | t^2+3tf-28f^2= | | 2x^3+2x-12=0 | | 15x-4z=20 | | 4.08(x+10)=9.50(x-2) | | 2y-8=7y+17 | | 3(r-6)+2=2(r+2)-21 | | 2(9n-1)+7(10+x)=35 | | 9x^8+18x^6=0 |